2018
DOI: 10.1002/jts.22305
|View full text |Cite
|
Sign up to set email alerts
|

Telemental Health Delivery of Skills Training in Affective and Interpersonal Regulation (STAIR) for Rural Women Veterans Who Have Experienced Military Sexual Trauma

Abstract: This pilot study assessed the feasibility, acceptability, and initial efficacy of a skills-focused treatment delivered via video teleconferencing (VTC) to women veterans living in rural areas who had experienced military sexual trauma (MST). The Skills Training in Affective and Interpersonal Regulation (STAIR) program focuses on teaching emotion management and interpersonal skills in 8 to 10 sessions. The STAIR program may be a good fit for individuals in rural areas for whom social isolation and low social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
2
43
0
2
Order By: Relevance
“…The STAIR program is an evidence-based therapy originally designed to treat people with post-traumatic stress disorder who were victims of childhood abuse (Cloitre et al 2010). The program was adapted to provide telemental health services to women veterans living in rural areas who have a history of military-associated sexual and other traumas (Weiss et al 2018). Participants receive evidenced-based treatment for post-traumatic stress disorder through individual or group teleconferencing available in local outpatient clinics or their own homes.…”
Section: Skills Training In Affective and Interpersonal Regulation (Smentioning
confidence: 99%
“…The STAIR program is an evidence-based therapy originally designed to treat people with post-traumatic stress disorder who were victims of childhood abuse (Cloitre et al 2010). The program was adapted to provide telemental health services to women veterans living in rural areas who have a history of military-associated sexual and other traumas (Weiss et al 2018). Participants receive evidenced-based treatment for post-traumatic stress disorder through individual or group teleconferencing available in local outpatient clinics or their own homes.…”
Section: Skills Training In Affective and Interpersonal Regulation (Smentioning
confidence: 99%
“…The STAIR program is a skills-based, eight to 12 session program that, in combination with trauma-focused work, has been shown in two randomized controlled trials (RCTs) to reduced PTSD, depression, and a range of other trauma-related symptoms (Cloitre, Koenen, Cohen, & Han, 2002;Cloitre et al, 2010). The results of a recent open trial study indicated that STAIR as a stand-alone therapy was effective in reducing symptoms of PTSD and depression in veterans, with effect sizes equivalent to those found for trauma-focused treatments, suggesting the potential benefits of non-trauma-focused treatment in reducing symptoms of PTSD and depression (Weiss, Azevedo, Webb, Gimeno, & Cloitre, 2018). The rationale for the development of STAIR was to enhance functioning, particularly social adjustment, through improved emotion management and social skills delivered via a therapy meant to complement trauma-focused work.…”
mentioning
confidence: 99%
“…This represents a potential benefit of the treatment, as it increases the pool of PCMHI staff who can offer services to individuals in need. The STAIR program is intuitive, well liked, and well tolerated (Weiss et al., 2018), and it may be particularly suited for delivery in non–mental health settings.…”
mentioning
confidence: 99%
“…Similarly, video and phone conferencing allow rural physicians to have ready access to trauma surgeons E389 for patient management and educational sessions. 28 Future studies examining the impact and utility of distance-based care will be critical to evaluate outcomes for rural trauma patients.…”
Section: Discussionmentioning
confidence: 99%